The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1177/1759720x20953357
|View full text |Cite
|
Sign up to set email alerts
|

Early steroid withdrawal has a positive effect on bone in kidney transplant recipients: a propensity score study with inverse probability-of-treatment weighting

Abstract: Background: Long-term corticosteroid use after kidney transplantation is associated with a decrease in bone mineral density (BMD) and a high fracture risk. We hypothesized that patients with early steroid withdrawal (ESW) would display a gain in BMD in the year following kidney transplantation, when compared with patients on long-term corticosteroid therapy. Methods: In a cohort of kidney transplant recipients, 356 patients were included between 2012 and 2019. Dual-energy X-ray absorptiometry was performed 1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…This is why we decided to assay serum UT concentrations upon transplantation, and might account for the lack of correlation between UT concentrations at the time of transplantation and changes in BMD at M12 and at M24. Furthermore, we have recently shown that corticosteroid use in general and exposure time in particular have an impact on BMD and on fracture incidence among kidney transplant recipients [10]. Secondly, the choice of BMD as a surrogate marker of bone health might not be the most appropriate because dual-energy X-ray absorptiometry (DXA) does not differentiate between cortical bone and trabecular bone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is why we decided to assay serum UT concentrations upon transplantation, and might account for the lack of correlation between UT concentrations at the time of transplantation and changes in BMD at M12 and at M24. Furthermore, we have recently shown that corticosteroid use in general and exposure time in particular have an impact on BMD and on fracture incidence among kidney transplant recipients [10]. Secondly, the choice of BMD as a surrogate marker of bone health might not be the most appropriate because dual-energy X-ray absorptiometry (DXA) does not differentiate between cortical bone and trabecular bone.…”
Section: Discussionmentioning
confidence: 99%
“…The decrease in BMD after kidney transplantation is generally attributed to the cumulative effect of corticosteroid treatment [7][8][9][10]. Other risk factors include the time on dialysis prior to transplantation, age at transplantation, vitamin D deficiency, and a low body mass index (BMI, <23 kg/m 2 ) [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…One of the most relevant risk factors is high doses or prolonged GC therapy [91,92] . Kidney transplant recipients with early steroid withdrawal showed higher bone mineral density in lumbar spine and femoral neck and less osteopenia [93] . On the other hand, one study followed 36 renal transplant patients who continued low daily dose of 5mg prednisolone from day 42 after transplantation onward for 1 year.…”
Section: Bone Disordersmentioning
confidence: 96%
“…Thus, for each decade of life, the risk of hip fracture is estimated to be 55% higher. Fortunately, the role of glucocorticoid use, an important risk factor for bone fractures, seems to be decreasing in transplant patients after new protocols with lower doses or shorter term are increasingly common [ 142 , 143 , 144 , 145 ].…”
Section: Bone Disease After Kidney Transplantationmentioning
confidence: 99%